Knowledge and attitudes toward repetitive transcranial magnetic stimulation (rTMS) as a treatment for postpartum and peripartum depression - H. Al-Shamali; N. Zinchuk; R. Yan; M. Jackson; M. Morrissette; A. Greenshaw; Y. Zhang (European Psychiatry, 2022)
Introduction Postpartum and peripartum depression are debilitating disorders that impact the mother and their ability to care for their children’s emotional, social, and physical needs. Current treatments include psychotherapy, pharmacotherapy, and electroconvulsive therapy. These treatments are moderately effective or come with side effects that can negatively impact mother and child. As a result, many mothers view some treatments as unacceptable while pregnant or breastfeeding. Over the last decade, repetitive transcranial magnetic stimulation (rTMS) has shown promise as an effective and safe treatment option for postpartum and peripartum depression. However, little is known regarding people’s knowledge and attitudes towards this emerging technology, with no research assessing this in Canada.